2012
DOI: 10.4149/gpb_2012_005
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and epigallocatechin gallate effects on the cell membranes biophysical properties correlate with their antioxidant potential

Abstract: Abstract. Quercetin and epigallocatechin gallate are two of the most abundant polyphenols in dietary plants, including apples, onions, red wine and green tea. The bioactivity of polyphenols is linked to their ability to interact with cell membranes without being internalized. The aim of the present study was to assess the short-time effect of these polyphenols on membrane anisotropy and transmembrane potential of U937 monocytes and Jurkat T lymphoblasts. Results showed that quercetin and epigallocatechin galla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…Many studies were devoted to the effect of flavonoids on the cell membrane, using different methods to assess membrane fluidity [10,21,47,48]. Steadystate fluorescence polarization of TMA-DPH bound to the cell membrane was used in this study, as the dye displays in isotropic media-specific fluorescence anisotropy properties, which are changed if the free orientation of the probe is restricted by the local microenvironment: membrane fluidity is proportional to the inverse of squared anisotropy [19,30,31]. Polyphenols could affect cell function by modifying plasma membrane structure and physical characteristics, such as fluidity and electrical properties [19,24,25,43,[47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies were devoted to the effect of flavonoids on the cell membrane, using different methods to assess membrane fluidity [10,21,47,48]. Steadystate fluorescence polarization of TMA-DPH bound to the cell membrane was used in this study, as the dye displays in isotropic media-specific fluorescence anisotropy properties, which are changed if the free orientation of the probe is restricted by the local microenvironment: membrane fluidity is proportional to the inverse of squared anisotropy [19,30,31]. Polyphenols could affect cell function by modifying plasma membrane structure and physical characteristics, such as fluidity and electrical properties [19,24,25,43,[47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…One cell aliquot constituted the control, the second was cultivated in presence of 10 µM quercetin, and the third was cultivated in the presence of 10 µM EGCG. Previous experiments showed that the small amount of DMSO in which quercetin was dissolved did not affect any of the investigated parameters [19].…”
Section: In Vitro Pbmc Treatmentmentioning
confidence: 99%
See 3 more Smart Citations